United States. Army. 82nd Airborne Division report - United States. Army. Airborne Division, 82nd.
Report pertaining to the actions of the 82nd Airborne Division in Central Europe during April and May 1945.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Europe